Communicative responses to jealousy in situations of the friendly triangulation - Shostak, Liudmila A. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The results of an empirical research of gender differences of communicative responses to jealousy in situations of the friendly triangulation from the position of a jealous individual and the object of his/her jealousy are considered. The author’s method «Communicative responses to jealousy in friendly relations», adapted and validated by I. A. Fourmanov and L. A. Shostak, was used in the research. The sample of the research includes 755 respondents aged between 18 to 22. The obtained results allowed to establish the leading communicative responses to jealousy in the following types of friendly triangles: partners and a competitor of the same sex; partners of the same sex and a competitor of the opposite sex to a jealous individual; partners of different sexes and a competitor of one sex with a jealous individual; partners of different sexes and a competitor of the opposite sex to a jealous individual. The research shows that an integrative communication and negative affective expression are the most frequently used responses in situations of friendly triangles, regardless of gender; the responses of compensation/substitution, an active distancing and avoidance/negation take a subordinate position.
Keywords: friendly jealousy; jealousy in a friendly triangulation; types of situations of jealousy in friendly triangles; communicative responses to jealousy; a jealous individual and the object of his/her jealousy; gender differences